Learning Media Based on Local History in Improving the Quality of Distance Learning - Wijaya, Ahmad Alim; Syarifuddin; Asmi, Adhitya Rol (Journal of Education Reseach and Evaluation, 2022)
Educators have attempted various strategies to make distance learning interesting and exciting. However, in the absence of proper preparation in terms of the use and utilization of technology, the efforts made by educators still need to be successful. The lack of attractiveness of distance learning by educators causes students to experience a decrease in their willingness and learning outcomes. This study aims to analyze audio-visual learning media's validity, practicality, and impact on student learning outcomes during distance learning. This study adopted the development research method using the ADDIE development model. The subjects of this study were 41 students and one educator who conducted distance learning on historical subjects. The results of the research obtained are audio-visual learning media based on local history with an average value of 4.34 in the very valid category and also feasible to be tested on students in distance learning. In addition, this learning media effectively influences student learning outcomes before and after using learning media by 45.5%. It proves that the local history audio-visual learning media effectively improves student learning outcomes in distance learning. The use of this learning media for distance learning depends on the facilities and infrastructure educators and students use. Therefore careful and appropriate preparation is needed to achieve an efficient and effective learning process.